HIV control through a single nucleotide on the HLA-B locus. - Kløverpris, H; Harndahl, M; Leslie, A; Carlson, J; Ismail, N; van der Stok, M; Huang, K; Chen, F; Riddell, L; Steyn, D; Goedhals, D; van Vuuren, C; et al. (2012)
Genetic variation within the HLA-B locus has the strongest impact on HIV disease progression of any polymorphisms within the human genome. However, identifying the exact mechanism involved is complicated by several factors. HLA-Bw4 alleles provide ligands for NK cells and for CD8 T cells, and strong linkage disequilibrium between HLA class I alleles complicates the discrimination of individual HLA allelic effects from those of other HLA and non-HLA alleles on the same haplotype. Here, we exploit an experiment of nature involving two recently diverged HLA alleles, HLA-B*42:01 and HLA-B*42:02, which differ by only a single amino acid. Crucially, they occur primarily on identical HLA class I haplotypes and, as Bw6 alleles, do not act as NK cell ligands and are therefore largely unconfounded by other genetic factors. We show that in an outbred cohort (n = 2,093) of HIV C-clade-infected individuals, a single amino acid change at position 9 of the HLA-B molecule critically affects peptide binding and significantly alters the cytotoxic T lymphocyte (CTL) epitopes targeted, measured directly ex vivo by gamma interferon (IFN-γ) enzyme-linked immunospot (ELISPOT) assay (P = 2 × 10(-10)) and functionally through CTL escape mutation (P = 2 × 10(-8)). HLA-B*42:01, which presents multiple Gag epitopes, is associated with a 0.52 log(10) lower viral-load set point than HLA-B*42:02 (P = 0.02), which presents no p24 Gag epitopes. The magnitude of this effect from a single amino acid difference in the HLA-A*30:01/B*42/Cw*17:01 haplotype is equivalent to 75% of that of HLA-B*57:03, the most protective HLA class I allele in this population. This naturally controlled experiment represents perhaps the clearest demonstration of the direct impact of a particular HIV-specific CTL on disease control.